(untitled) (Research, Society and Development, 2021)
This text grew out of the need to understand the different approaches that underlie teaching and the act of teaching as part of the realization of formal education. Therefore, the general objective of this study is to demonstrate the main approaches to teaching and teaching practice in relation to pedagogical trends. As specific objectives we enumerate a) to present an approach to the ideas about the teaching profession and the knowledge of teaching; b) highlight the formal, prescriptive, and normative theories of teaching and c) discuss the main pedagogical trends. It is a qualitative research of the bibliographic, bibliometric and content analysis type and was based on the contributions of the following theorists: Gauthier; Martineau; Desbiens, Malo & Simard (1997); Gage (2009); Perrenoud, Thuler, De Macedo, Machado & Allessandrini, (2002). Among the results, we noticed that the different pedagogical currents that exist demonstrate the wide variety of thoughts that the teacher needs to know in order to appropriate some or more in his career as a teacher.